Answer:
1. f(–9) = -66 , g( 1 ) = 27 (Please double-check your given options, there must have been a typographical error for Option C for g( 1 ) = 29). g( 1 ) is supposed to be 27.
2. Option A: f(–9) = 25, g(–1) = 21
Step-by-step explanation:
1.Find the value of f(–9) and g(1) if f(x) = 8x + 6 and g(x) = 9x + 20x−2
f(x) = 8x + 6
f(–9) = 8(-9) + 6 = -66
g(x) = 9x + 20x − 2
g( 1 ) = 9( 1 ) + 20( 1 ) − 2 = 27
None of the given choices were correct (unless there's a typo error for Option C — it's supposed to be g( 1 ) = 27 instead of 29?) because the correct answers are: f(–9) = -66 and g( 1 ) = 27
2. f(–9) and g(–1) if f(x) = –3x – 2 and g(x) = 3x³ – 24x
f(x) = –3x – 2
f(–9) = –3(–9) – 2 = 25
g(x) = 3x³ – 24x
g(–1) = 3(–1)³ – 24(–1) = 21
Therefore, the correct answer is Option A: f(–9) = 25, g(–1) = 21